2015
DOI: 10.1177/1356336x15574367
|View full text |Cite
|
Sign up to set email alerts
|

Role socialization theory

Abstract: Much has been learned about the socialization of physical education (PE) teachers using occupational socialization theory (OST). However, important to understanding any socialization process is explaining how the roles that individuals play are socially constructed and contextually bound. OST falls short of providing a comprehensive overview of how the role of the PE teacher is defined and negotiated within schools. The purpose of this paper is to present role socialization theory as a new approach to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(24 citation statements)
references
References 66 publications
0
23
0
1
Order By: Relevance
“…Further, in many contexts, physical education is misunderstood and positioned as marginal to the primary mission of schooling (Laureano et al, 2014). Nevertheless, a variety of sociopolitical factors operating at the local level and those that are informed by public policy and popular opinion frame the ways in which physical education is viewed (Richards, 2015). Educational policies, for example, can serve to either elevate the status of physical education or institutionalize marginality (Lawson, 2018).…”
Section: Occupational Socialization Theory and Pathways Into Teachingmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, in many contexts, physical education is misunderstood and positioned as marginal to the primary mission of schooling (Laureano et al, 2014). Nevertheless, a variety of sociopolitical factors operating at the local level and those that are informed by public policy and popular opinion frame the ways in which physical education is viewed (Richards, 2015). Educational policies, for example, can serve to either elevate the status of physical education or institutionalize marginality (Lawson, 2018).…”
Section: Occupational Socialization Theory and Pathways Into Teachingmentioning
confidence: 99%
“…suggested that physical education should be defined "by what is said, done, and written in its name" (p. 1). To a large degree, what is done in the name of physical education in PETE programs is shaped by the faculty members teaching within those programs (Richards, 2015). Nevertheless, there seems to be some general consensus among PETE faculty members across countries that physical education should focus on the preparation of youth for a lifetime of meaningful engagement with physical activity (McEvoy, Heikinaro-Johansson, & MacPhail, 2017).…”
Section: Interaction Between Acculturation and Professional Socializamentioning
confidence: 99%
See 1 more Smart Citation
“…The task is heavier owing to the number of students per class, a teaching task divided among several schools and the teacher's involvement in extracurricular activities (Aubin, 2017;Cruz & Li, 2009), not to mention the isolation of PHE teachers (Leroux, Beaudoin, Grenier, Turcotte, & Rivard, 2016). The physical environment, which plays a key role during the TI of PHE teachers, may present problems including outdated or lack of sports equipment, a space that's too small or poorly adapted to groups of students (Demirhan et al, 2014) and a work area physically isolated from the school's other teaching areas (Aubin, 2017;Parker, Patton, & Tannehill, 2012;Richards, 2015). As well, the PHE teacher becomes aware that the subject is marginalized (Henninger, 2007) and viewed as less important by both the administrators (Aubin, 2017;Demirhan et al, 2014) and the students (Eldar, Nable, Schechter, & Marzin, 2003).…”
Section: Key Teacher Induction Challenges In Physical and Health Educmentioning
confidence: 99%
“…These phases reflect the influence of individual biographies before TE, teacher training in higher education and work socialization in the context of schools and are fully described and analysed in comprehensive research reviews (Pike & Fletcher, 2014;Richards et al, 2014;Schempp & Graber, 1992;. The unique contextual features of schools and teaching ought to be recognized, even though the theoretical framework was originally based on the context of the United States (Pike & Fletcher;Richards, 2015). Therefore, research is needed outside the traditional arena to confirm or challenge existing findings.…”
Section: Occupational Socialization Theory As Theoretical Frameworkmentioning
confidence: 99%